The role of MRI for clinically suspected appendicitis during pregnancy - Zilio, André Luis Bergamaschi; Duarte, Juliana Avila; Souza, Fabricio Bergelt; Santos, Letícia Maffazzioli (Clinical and Biomedical Research, 2016)
A 31 years female with approximately 20 weeks of gestation attends the emergency department of the Hospital de Clínicas de Porto Alegre (HCPA) reporting pain in the lower abdomen radiating to the right iliac fossa. After clinical and laboratory examination, the clinical diagnosis of appendicitis was suspected, and then performed magnetic resonance imaging (MRI) of the abdomen for diagnostic reasons. The MRI of the abdomen was performed and revealed signs of appendicitis. The intraoperative findings were purulent fluid in the right iliac fossa and appendix with necrotic appearance without signs of perforation. The pathological diagnosis was acute suppurative appendicitis, with periviscerite signals. In pregnant women the enlarged uterus can alter the position of the abdominal contentes and thus make sonography and clinical diagnosis more difficult. CT can be performed in such cases, but it involves a considerable amount of radiation. A typical dose for an abdominal CT examination is on the order of 10 mSv. The routine use of diagnostic CT for benign diseases, as in appendicitis, raises the question whether the diagnosis can be obtained by other radiologic means, especially in pregnant women and even more when the fetus is in the direct beam. The International Commission on Radiological Protection recently published a report on radiation and pregnancy. They recommended that if the expected dose for the fetus is high, one should question whether the diagnosis could be obtained without using ionizing radiation. MRI has been described as a valuable technique for the evaluation of patients with suspected acute appendicitis.